Calibration and experiment of discrete element model parameters of Zanthoxylum bungeanum - Wang, Jian; Chen, Lin; Tang, Yingwen; Chen, Zhifan; Wu, Qingsong; Han, Dandan (Frontiers in Mechanical Engineering, 2023)
Zanthoxylum bungeanum is an essential condiment in Chinese cuisine, and it is also a kind of economic crop which contributes a lot to people's income especially in poor areas. At the present, the simulation and calibration of Zanthoxylum bungeanum particle parameters are lack of research. Therefore, this study focused on using EDEM software to simulate and calibrate the parameters of Zanthoxylum bungeanum granules. Firstly, a modeling method of Zanthoxylum bungeanum granules was proposed, and the discrete element model of Zanthoxylum bungeanum granules was established. Then the Poisson's ratio and elastic modulus of Zanthoxylum bungeanum granules were determined through experiments, and the coefficient of restitution, static friction coefficient and rolling friction coefficient between Zanthoxylum bungeanum granules and the Dragon skin30 silicone tablet were measured. After that, EDEM simulation was used to determine various simulation parameters between Zanthoxylum bungeanum granules and materials. The Angle of repose simulation tests were applied to measure and calibrate the intrinsic parameters and contact parameters of Zanthoxylum bungeanum granules. By comparing the physical test results of the angle of repose of Zanthoxylum bungeanum granules with the simulation test results, the feasibility of the discrete element modeling method of Zanthoxylum bungeanum granules proposed in this paper is verified. With this research, designers and engineers can use the simulation model developed in this work to design and optimize Zanthoxylum bungeanum picking machines. Needless to mention, it would have a significant impact on the food industry in China and other countries where Zanthoxylum bungeanum is widely used.